Cardiovascular and metabolic requirements of water polo - Platanou, T. (Serbian Journal of Sports Sciences, 2009)
This study is a review of literature related to the energy mechanisms that are used duringa water polo game, and it also provides the structure of technical and tactical game activities ofwater polo players so that useful training conclusions can be drawn. Based on the evidence derived from this review, the mechanisms responsible for the availability of water polo energy and the percent contribution of the aerobic and anaerobic mechanisms rely on the methodological approach and the defensive system of the game. However, as it appears in all of the studies reviewed, the aerobic as well as the anaerobic alactic mechanisms predominate over the anaerobic lactate mechanism. In addition, this review demonstrates that the intensity of the game is reduced, resulting in the increase of the contribution of the aerobic and, in parallel, the decrease of the anaerobic mechanism, in the following situations: 1) in the last minutes of the 4 x 9 minutes' periods in comparison to the 4 x 7 minutes' periods; 2) in the last period of the game compared to the first periods in contrast to the goalkeeper's performance intensity which does not differ from period to period; 3) in games with lower levels of competitiveness compared to the games of higher level; while 4) there are no differences in the intensity of the game (energy requirements) between players of different positions and different levels even though players of a higher level swim considerably faster. For the water polo training plan, the primary informative sources need to be taken into consideration, i.e. the physiological demands of the game based on the differences in game durations, the period of the game, the level of competitiveness of the players, the level of competitiveness of the teams, and the different player positions.